Silviculture for forest management in Nepal - Poudel, K. C. (Banko Janakari, 2018)
Forests and trees have social, ecological and economic importance to humankind. It is high time to manage worlds’ forests sustainably to ensure supply of forest based goods and services and reduce the adverse impacts of climate change. This paper highlights the history and current status of forest management, challenges and opportunities, various approaches adopted in forest management and recent initiatives in sustainable and scientific forest management (SFM) in Nepal. About one-third of the total 6.61 million ha (45%) of Nepal’s forest has been handed over to over 30,000 forest user groups. Various failed attempts in forest management in the past were mainly due to lack of institutional capacity, political back-up, conflict, etc. “Forestry for Prosperity” - a new vision announced at the 10th National Conservation Day in 2012, re-introduced the concept of sustainable and scientific forest management and launched this in ten districts with designated program and budget in the same year. Accordingly, forest blocks are identified, inventoried, management plans drawn and implemented. Over 69, 000 ha forests in 11 districts are under silviculture management to date. Thus managed forests show profuse regeneration, improved supply of forest products, increased revenue, improved forest health and enhanced capacity of forestry professionals. Yet, lack of political and professional commitment, inadequate human and financial resources, and weak institutional and professional competency are specific challenges to SFM in Nepal. Creating enabling environment, institutional reorganization, enhancing forest management capacity, improved forestry governance, reducing non-forestry workload of government forestry staff, and preparation and use of standard silvicultural operational guidelines have been suggested to upscale SFM in Nepal. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page : 15-20